Psychological barriers of inclusive interaction - Slusareva, Yelena
The “inclusive” populations contain a great difference in sensory, cognitive and physical user capabilities, particularly when non-age-related impairments are taken into account. While this population is growing, the most productive research and strategy sector is unavoidably shrinking in part to that growth. The article presents an analysis of the psychological barriers that arise in the process of inclusive interaction. The mechanisms of barriers’ genesis are substantiated: objective barriers determined by the presence of health limitations (biosensor disturbances) and subjective ones caused by the intrapersonal characteristics of the partners in the interaction.
Keywords: Psychology